enviroMETS Lighthouse Projects: a strategic pathway to high-value sustainable post-mining land use - Morton, A; Merz, R (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
This paper presents an overview of the enviroMETS (Qld) Lighthouse Projects (LHP) initiative, which aims to find innovative and sustainable ways to make mining-impacted land valuable to its current and future custodians. The evolving LHP strategy outlines the overall approach and objectives in delivering societal, economic, and environmental stakeholder outcomes by shining a light on what can be achieved. The project principles, derived from collaborative and inclusive planning, emphasise the importance of leveraging the innovation ecosystem, leading the mining equipment, technology and services (METS) sector and quantifying non-financial value. The key challenges and research priorities of the LHP initiative were identified through a perception survey and online member poll which made clear that technological developments could only be pursued with a clarified regulatory authorisation pathway, and the availability of a multi-factor business case for viable public/private investment. A later survey confirmed the LHP strategy to develop multiple pilot sites was on track and sound. The paper discusses the outcomes that can be achieved through collaboration, including generating ongoing funds for site rehabilitation, identifying viable business cases and creating sustainable economic development. Additionally, the paper explores the potential for nature-positive outcomes, local employment generation and reduced regulatory hurdles associated with rehabilitation opportunities. The LHP initiative consists of three investigative research projects: regulatory pathway mapping, post-mining land use business case methodology and the development of investible pilot sites. These projects navigate the regulatory framework impacting economic transformation, develop a reliable methodology for assessing the net best value of post-mining land use options and establish pilot sites to prove new innovative economic purposes. The paper highlights the progress made in each of these projects and the importance of collaboration with stakeholders, including government agencies, mining operators and regional communities. The paper concludes by discussing the strategic steps necessary for the establishment of multiple pilot sites across Queensland and the attraction of investors for remaining and repurposed mining land.
Keywords: post-mining land use